influence of foot care education with a Media Flip Chart against the change in the client behaviour of Diabetes mellitus - Handono Fatkhur Rahman; Aditya Wahyu Santoso; Heri Siswanto (Jurnal Nasional Ilmu Kesehatan, 2020)
Increased incidence of DM wounds is caused by the treatment of Ungood diabetes, which is at risk of nerve damage, leading to the deterioration of blood flow and causing numbness in the legs. Research aims to determine the influence of foot care education with Flip Chart media against changes in the behavior of Diabetes mellitus client. The research method used quantitative research with pre-experimental type one-group pretest-posttest with a sample number of 40 people with Accidental Sampling technique. Results of the study showed the mean of knowledge before being given foot care education is from 10.05 and after being given foot care education to 15.63 and ρ value (0,000 < 0.05), while the mean action before being given foot care education is from 7.13 And after being given foot care education to 10.50 and ρ value (0,000 < 0.05) and mean attitude before given foot care education is from 33.40 and after being given foot care education to 39.53 and ρ value (0,000 < 0.05). And the result of mean behavior before being given foot care education is 50.58 and mean behavior after being given foot care education to 65.65 and ρ value (0,000 < 0.05). It can be concluded that there is the influence of foot care education with Flip Chart media to change the behavior of the client Diabetes mellitus. So foot care education is strongly advised to be given to diabetes mellitus clients.